Goatweed Flower Extract (Ageratum conyzoides L.) as A Botanical Insecticide for Pest Control Crocidolomia binotalis Z. - Nurhidayat, Setia P.; Rusdi, Nurul; Ulinuhayani, Muhammad; Singgih, Bambang; Triono, Budi (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2024)
Crocidolomia binotalis Z. is an important cabbage plant pest in Indonesia. Nevertheless, pest control strategies depend on synthetic pesticides, negatively impacting ecosystems.Therefore, developing an effective organic pesticide approach to controlling C. binotalis is necessary. This research aimed to test the effectiveness of goatweed flower extract (Ageratum conyzoides L.) in controlling pest C. binotalis. The research consisted of two sets of experiments with two methods: the stomach and contact poison. Each experimental set was arranged in a completely randomized design (CRD) with three replications. The treatments were six levels of extract concentration at 0%, 15%, 30%, 45%, 60%, and 75%. The results showed that the application of A. conyzoides flower extract using the stomach and contact poison methods significantly increased the percentage of larval mortality 24 hours after application (haa) and the percentage of total larval mortality. The flower extract treatment of A. conyzoides significantly reduced the percentage of leaf area eaten, increased larval mortality, inhibited pupation and imago emergency, and shortened the larval stage's duration. The percentage of larval mortality through contact poison was higher than stomach poison.